Wise Social Media Education Based on the ITE LAW at SMP Negeri 12 Denpasar - I Wayan Werasmana SANCAYA; I Komang Adi Kurniawan SAPUTRA; I Gede Wira DARMA (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology has had a significant impact on student interaction patterns at the junior high school level. Social media has become a primary platform for students to communicate, but on the other hand, minimal digital literacy and poor legal understanding make them vulnerable to negative behaviors such as spreading hoaxes, cyberbullying, and violating communication ethics. This community service activity aims to provide wise social media education based on the Electronic Information and Transactions Law (UU ITE) to students of SMP Negeri 12 Denpasar. The implementation method included interactive seminars, group discussions, and case study simulations designed with a participatory approach. Evaluation was conducted through pre- and post-tests to measure improvements in students' knowledge and behavioral reflections. The results of the activity showed a significant increase in students' understanding of digital literacy from 45% to 82% and knowledge of the ITE Law from 20% to 75%. In addition, students' attitudes towards cyberbullying and negative content on social media experienced positive changes, as reflected in their increased awareness of not spreading hoaxes, avoiding hate speech, and using social media more responsibly. This program not only improves students' understanding but also benefits schools and parents by supporting their children's digital activities. Therefore, this activity serves as a model that can be replicated in other schools to strengthen digital literacy, legal awareness, and develop wise social media character among teenagers.Perkembangan teknologi digital telah membawa dampak signifikan terhadap pola interaksi siswa di tingkat sekolah menengah pertama. Media sosial menjadi ruang utama bagi siswa untuk berkomunikasi, namun di sisi lain, minimnya literasi digital dan rendahnya pemahaman hukum membuat mereka rentan terjebak dalam perilaku negatif seperti penyebaran hoaks, cyberbullying, serta pelanggaran etika komunikasi. Kegiatan pengabdian masyarakat ini bertujuan untuk memberikan edukasi bijak bermedia sosial berbasis Undang-Undang Informasi dan Transaksi Elektronik (UU ITE) kepada siswa SMP Negeri 12 Denpasar. Metode pelaksanaan meliputi seminar interaktif, diskusi kelompok, dan simulasi studi kasus yang dirancang dengan pendekatan partisipatif. Evaluasi dilakukan melalui pre-test dan post-test untuk mengukur peningkatan pengetahuan serta refleksi perilaku siswa. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada pemahaman literasi digital siswa dari 45% menjadi 82% serta pengetahuan mengenai UU ITE dari 20% menjadi 75%. Selain itu, sikap siswa terhadap cyberbullying dan konten negatif di media sosial mengalami perubahan positif, yang tercermin dari meningkatnya kesadaran mereka untuk tidak menyebarkan hoaks, menghindari ujaran kebencian, dan menggunakan media sosial secara lebih bertanggung jawab. Program ini tidak hanya meningkatkan pemahaman siswa, tetapi juga memberi manfaat bagi sekolah dan orang tua dalam mendampingi aktivitas digital anak. Dengan demikian, kegiatan ini menjadi model yang dapat direplikasi di sekolah lain guna memperkuat literasi digital, kesadaran hukum, serta pembentukan karakter bijak bermedia sosial di kalangan remaja.